Phenotypic and functional characterisation of myofibroblasts, macrophages, and lymphocytes migrating out of the human gastric lamina propria following the loss of epithelial cells. Issue 3 (1st March 1999) - Wu, K C; Jackson, L M; Galvin, A M; Gray, T; Hawkey, C J; Mahida, Y R
Abstract : BACKGROUND: The basement membrane of human colonic mucosa contains numerous discrete pores. We have recently shown that following loss of the surface epithelium, many cells migrate out of the colonic lamina propria via basement membrane pores. AIMS: To characterise cells migrating out via basement membrane pores of the human gastric lamina propria, following loss of the surface epithelium. METHODS: Fresh human gastric mucosal samples were completely denuded of epithelial cells and placed in culture. Tissue samples were studied by electron microscopy (EM) and cells by EM, FACS analysis, immunohistochemistry, and reverse transcription polymerase chain reaction (RT-PCR). RESULTS: EM showed numerous discrete pores (0.65–8.29 μm in diameter) in the subepithelial basement membrane. During culture of mucosal samples denuded of epithelial cells, lymphocytes, macrophages, and myofibroblasts migrated out of the lamina propria via the basement membrane pores. The lymphocytes were predominantly CD45RO+ and CD69+ T cells. Macrophages were shown to express cyclooxygenase (COX) 1 and 2 enzymes. Myofibroblasts were established in culture and, despite prolonged culture and passage, retained their phenotype. They expressed mRNA and protein for COX 1 and 2 enzymes and their release of prostaglandin E2 was inhibited by selective COX 1 and 2 inhibitors. CONCLUSIONS: Lamina propria cells migrating out of cultured denuded gastric mucosal samples have been characterised phenotypically and functionally. Such cells would be suitable for studies of their interactions with epithelial cells and also with Helicobacter pylori and its products.